Peningkatan Kemampuan Adaptasi Pola Belajar Siswa Melalui Support Group di SMP Negeri X - Kelin Karpillia Tadius; Santi Esterlita Purnamasari (PT. Giat Konseling Nusantara, 2026)
The transition period from Elementary School to Junior High School is often associated with adjustment difficulties among students in academic, social, and emotional aspects. Based on the assessment conducted at SMP Negeri X, seven students of class 7X were identified as experiencing difficulties in adapting to the learning system in junior high school, such as lack of focus during lessons, failure to complete assignments, passive behavior in classroom discussions, and difficulties in building social relationships with peers. This community service program aimed to improve students’ learning adaptation skills through a support group intervention based on the Mutual Aid Support Group Model developed by Lawrence Gitterman and Lee Shulman. The intervention was conducted through five sessions, namely engagement, exploration, mutual support, skill practice, and reflection and termination. In addition, students were asked to complete daily journals for 30 days to monitor behavioral changes, self-regulation, and adjustment abilities in daily life. The evaluation was carried out using a pre-test and post-test design with the Self-Adjustment Scale. The results showed an improvement in self adjustment scores among all participants after the intervention. Furthermore, observations and interviews with the school counselor and homeroom teacher indicated positive behavioral changes, including increased participation in learning activities, better emotional regulation, improved discipline, and greater involvement in group discussions. The results of the reflective journals also demonstrated that students were able to manage their daily activities more systematically through the implementation of simple daily schedules. Therefore, the mutual aid based support group proved to be effective as a preventive intervention in helping students improve their adaptation to academic and social demands within the school environment.